Comparison of Soluble Guanylate Cyclase Stimulators and Activators in Models of Cardiovascular Disease Associated with Oxidative Stress - Costell, Melissa H.; Ancellin, Nicolas; Bernard, Roberta E.; Zhao, Shufang; Upson, John J.; Morgan, Lisa A.; Hauk, Kristeen; Olzinski, Alan R.; Ballard, Victoria L.; Herry, Kenny; Grondin, Pascal; Dodic, Nerina; et al. (Frontiers in Pharmacology, 2012)
Soluble guanylate cyclase (sGC), the primary mediator of nitric oxide (NO) bioactivity, exists as reduced (NO-sensitive) and oxidized (NO-insensitive) forms. We tested the hypothesis that the cardiovascular protective effects of NO-insensitive sGC activation would be potentiated under conditions of oxidative stress compared to NO-sensitive sGC stimulation. The cardiovascular effects of the NO-insensitive sGC activator GSK2181236A (a non-depressor dose and a higher dose which lowered mean arterial pressure [MAP] by 5-10mmHg) and equi-efficacious doses of the NO-sensitive sGC stimulator BAY 60-4552 were assessed in Sprague Dawley rats during coronary artery ischemia/reperfusion (I/R) and spontaneously hypertensive stroke prone rats (SHR-SP) on a high salt/fat diet (HSFD). In I/R, neither compound reduced infarct size. In SHR-SP, HSFD increased MAP, urine output, microalbuminuria and mortality, caused left ventricular hypertrophy and impaired endothelium-dependent vasorelaxation. The low dose of BAY 60-4552 but not GSK2181236A decreased urine output and mortality. Conversely, the low dose of GSK2181236A attenuated cardiac hypertrophy. The high doses of both compounds similarly attenuated cardiac hypertrophy and mortality. In addition, the high dose of BAY 60-4552 reduced urine output, microalbuminuria and MAP. Neither compound improved endothelium-dependent vasorelaxation. In SHR-SP aorta, the vasodilatory responses to the NO-dependent compounds carbachol and sodium nitroprusside were attenuated by HSFD. In contrast, the vasodilatory responses to GSK2181236A and BAY 60-4552 were unaltered by HSFD, indicating that reduced NO-bioavailability and not changes in the sGC oxidative state is responsible for the vascular dysfunction. In summary, GSK2181236A and BAY 60-4552 provide partial benefit against hypertension-induced end organ damage. The differential beneficial effects observed between these compounds could reflect tissue-specific changes in the sGC oxidative state.